Kepercayaan Sebagai Moderasi Kepemimpinan Berbudi Luhur terhadap Kesejahteraan Karyawan - Tuti Sulastri; Delyana Rahmawany Pulungan; Rumintar J. H Marpaung; Alfa Santoso Budiwidjojo Putra; Ambar Kusuma Astuti (Jurnal Informatika Ekonomi Bisnis, 2024)
This long-standing lack of attention to and knowledge of virtuous character may explain why many leaders attempt to get ahead by making mistakes and why virtuous character traits often do not play a significant role in the training and evaluation of leaders. A possible reason for the lack of studies on the virtuous character of a leader is the lack of clarity of definition; Moreover, some scholars consider Virtue as well as good character to be too abstract and general to measure. This research aims to overcome the lack of research on the role of a leader's virtuous leadership on employee welfare. This research also adds the moderating variable trust in virtuous leaders. This research uses a quantitative approach with an explanatory research design. Data collection techniques were carried out using surveys. The research population consisted of 200 employees spread across Indonesia. And the analysis technique uses Smart PLS. The results of this research have found that virtuous leadership influences employee welfare, and trust as moderation is able to moderate virtuous leadership on employee welfare.